The isotopic composition of Zn in natural materials - Ghidan, Osama Yousef Ali (Curtin University, 2008)
This work represents the most recent development of Zn isotopic measurements, and the first identification of Zn isotopic fractionation in natural materials using Thermal Ionisation Mass Spectrometry (TIMS). The procedures developed in this research systematically evaluates and solves several critical analytical issues involved in TIMS Zn isotopic measurements such as, reducing the size of sample needed to perform an accurate and precise measurement, minimizing the effect of interferences on the Zn fractionation, reducing the blank associated with the analyses, dissolution and purification of different natural samples, and the generally ignored issue of the effect of the ion exchange chemistry (Zn separation) to the fractionation of Zn. These procedures have allowed sub-permil fractionations in the isotopic composition of Zn to be revealed in small Zn sample (1µg), and the determination of low level (ng) elemental abundance of Zn in samples to be measured accurately by the means of isotope dilution mass spectrometry IDMS. This thesis uses the rigorous double spike technique to measure fractionation, relative to the internationally proposed absolute Zn isotopic reference material (δ zero), based on a high purity Alfa Aesar 10759, now available to the international isotope community. All the isotopic measurements in natural materials were performed on bulk samples purified by ion exchange chemistry.The isotopic composition of the Zn minerals and igneous rocks agreed with that of the absolute reference material, which makes it possible to consider this reference material as being representative of “bulk Earth” Zn. Significant and consistent fractionation of ~+0.3 ‰ per amu were found in 5 sediments from a range of localities. The consistency of this is attributed to conveyor type oceanic circulations effects. The results from the two metamorphic samples indicate that the fractionation of Zn in these rocks is the same as found in igneous rocks but are different from the Zn found in sedimentary rocks. This supports the widely held assumption that high temperature and pressure processes do not fractionate the isotopic composition of chalcophile elements, such as has been found for Cd. Clay sample TILL-3 appears to exhibit a consistently slightly positive Zn fractionation of +0.12 ± 0.10 ‰ amu-1, although inside the uncertainties of both igneous and sedimentary rocks, which is not surprising since Till is thought to be a formed from a range of mixed glacial sediments The isotopic composition of Zn was measured in two plants and one animal sample. The fractionation of (-0.088 ± 0.070 ‰ amu-1) of Zn in the Rice (a C3 type plant material) sample suggested that Zn may be used to study Zn systematics in plants. The result obtained for MURST-Iss-A2 (Antarctic Krill) was +0.21 ± 0.11 ‰ amu-1 relative to the laboratory standard which is similar to the average Zn fractionation results of +0.281 ± 0.083 ‰ amu-1 obtained for marine sediments.In this work, the isotopic composition of Zn was measured in five stone and two iron meteorites. The range of Zn fractionation in stone meteorites was between -0.287 ± 0.098 and + 0.38 ± 0.16 ‰ amu-1, and was consistent with previous work, although more measurements would be needed to generalize this to all stone meteorites. In iron meteorites; Canyon Diablo was found to have the greatest fractionation of +1.11 ± 0.11 ‰ amu-1 relative to the laboratory standard. Of all the meteorites studied, Redfields clearly showed an anomalous isotopic composition indicating that this meteorite possesses a significantly different Zn isotopic composition compared to all of the other natural materials measured. Using 64Zn as a reference isotope, significant differences relative to the laboratory standard were found of +5.6 ± 0.4‰, +4.4 ± 3.6 ‰, and +21.0± 0.9 ‰ and +27.4 ± 18.8 ‰ on 66Zn and 67Zn, 68Zn and 70Zn respectively. These significant “Redfields anomalies” can be interpreted in a number of ways in relation to their nucleosynthetic production. Whether Redfields is a primitive type of iron meteorite or not, the Redfields anomaly strongly suggests wide spread isotopic heterogeneity of at least one part of the Solar System and does not support the suggestion that “Zn was derived from an initially single homogeneous reservoir in the early Solar System”. A pilot study to determine the concentration and the isotopic composition of Zn in River and tap water was performed.The concentration of Zn in River water averaged 6.9 ± 0.8 ngg-1, while for tap water it ranged from 13.1 ngg-1 to 5.2 μgg-1. River water was fractionated by -1.09 ± 0.70 ‰ amu-1, while restrained tap water yielded the maximum fractionation of -6.39 ± 0.62 ‰ amu-1 relative to the laboratory standard. The Zn fractionation of tap water is much larger than all other natural samples, although the uncertainty is also significantly greater due to the use of the less precise Daly detector used for these preliminary experimental measurements. The fractionation of Zn in seven ultra pure Zn standard materials was measured relative to the laboratory standard and found to range from -5.11 ± 0.36 ‰ amu-1 for AE 10760 to +0.12 ± 0.16 ‰ amu-1 for Zn IRMM 10440. There appears to be some evidence for a relationship between Zn fractionation and its purity. As well as natural materials, the fractionation of Zn was measured in a number of processed materials. None of these results or those obtained for natural materials impact on the currently IUPAC accepted value for the atomic weight of Zn. Along with fractionation determinations, the concentration of Zn was also measured by Isotope Dilution Mass Spectrometry in all of the samples. The concentration of Zn in five stony meteorites ranged from 26 ± 13 to 302 ± 14 μgg-1 for Plainview and Orgueil respectively. For ordinary Chondrites, the concentration of Zn in the three samples analysed ranged from 26 ± 13 to 64 ± 34 μgg-1 for Plainview and Brownfield 1937 respectively.The concentration of Zn was measured in two metamorphic rocks standard materials; the maximum concentration was 101.5 ± 1.7 µgg-1 in SDC-1. The concentration of Zn present in plant samples studied in this research was 22.15 ± 0.42, 14.62 ± 0.27 µgg-1 for Rice IMEP-19 and Sargasso NIES-Number 9 respectively which is within the normal range of Zn concentrations. Except for meteorites, the final uncertainties consistently cover the ranges of individual concentration measurements and indicate the homogeneity of the samples, including samples from different bottles where available. The final fractional uncertainties obtained for SRMs were all less than 2.8 %, demonstrating the high level of precision possible using IDMS.